Antroponymic contamination as political time marker (on a material of German language) - A. G. Golodov (Омский научный вестник: Серия "Общество. История. Современность")
Contamination as a kind of language game is a verbal response to present-day events, crisis situations and exciting episodes in political and social life. All of them based on the name Tramp (German variant of the English Trump) are of negative connotation in the German language. It gives rise to negative perception of antroponymic contaminants on the bases of the name of the American president by a «German ear». A strong extra-linguistic factor is added i.e. negative perception of Trump firstly as a candidate and later of his personality as a president, a politician not corresponding to «transatlantic picture of the world» of the German political leaders and mass media serving its interests. The use of antroponymic contaminants based on the name of Trump is not very numerous. But they shoot the target like a gun. That is why they are considered to be significant linguistic marks of the political period